Self-perception of non-cognitive skills among undergraduate health students during Covid-19 - Leal,Gilberto da Cruz (2021)
Abstract: Introduction: The social isolation in Brazil imposed in response to the COVID-19 pandemic has changed the way in which many undergraduate students have been learning, especially those involved in academic activities, as they now have remote rather than in-person classes. These changes may be beneficial if one considers this time favorable for improving non-cognitive skills, such as self-knowledge, resilience, collectivity, versatility, adaptability and leadership. Objective: This study was aimed at investigating how undergraduate health students in Southeastern and Southern Brazil perceived improvement in non-cognitive competencies during the rapid changes imposed in response to the COVID-19 pandemic. Method: This study evaluated 954 undergraduate health students at Brazilian higher education institutions. An online questionnaire consisting of 25 items was used to collect demographic and academic data as well as the subjects’ perception of non-cognitive feelings and skills during the remote continuation of the undergraduate course. The undergraduate health students’ perceptions were measured using a 10-point Likert intensity scale ranging from “very little” to “very much”. This questionnaire was previously validated in a group of 20 undergraduate students attending different health courses at a higher education institution in the State of São Paulo. Result: Correspondence analysis demonstrated that non-cognitive skills, including feelings, were perceived with varying intensities by the undergraduate students, thus making it possible to observe positive and negative impacts resulting from the changes they experienced. Students in the first and second semesters of their first year of studies tended to show lower collaboration scores than students in the third and fourth semesters; on the other hand, students in the first semester tended to show higher scores of openness to new experiences than students in the subsequent semesters. Conclusion: Overcoming procrastination, taking the lead in their studies, collaborating with peers, and being open to the new were the non-cognitive skills that were strongly perceived during the pandemic. In addition, frustration, lack of motivation, and emotional instability were strongly felt by the students, who considered that the COVID-19 pandemic had negatively affected their performance.